Descriptive Study of Students' Critical Thinking Skills on Controversial Environmental Issues Through Student Worksheets - Auliah*, Army; Jusniar, Jusniar; Fadly, Dewiyanti; Samada, Lukmanul Hakim (Jurnal IPA & Pembelajaran IPA, 2025)
Students' low critical thinking on controversial environmental issues reflects weak skills in analyzing and concluding information, worsened by the absence of effective learning tools such as student worksheets (LKM) designed to foster critical thinking skills. The purpose of this article is to describe and test the extent to which the use of LKM can affect students' critical thinking skills (CTS) in understanding and responding to controversial environmental issues. By understanding the influence of LKM on CTS, it is hoped that more effective strategies can be found in integrating environmental education into the higher education curriculum. The type of research in this article is descriptive qualitative. Data collection techniques through observation and document analysis. The data analysis process begins by reading observation notes and worksheet documents repeatedly to identify aspects of CTS that are identified. These aspects are then organized based on categories that are relevant to the research objectives. Furthermore, comparing data from various sources (observations and documentation) to ensure consistency of findings and increase the validity of the research results. The results of the study indicate that the use of worksheets is effective in improving students' CTS on controversial environmental issues, as shown by an increase in the quality of discussions and arguments that are more structured and in-depth